Nanofibrillar peptide hydrogels for self-delivery of lonidamine and synergistic photodynamic therapy. (1st January 2023) - Wu, Can; Jiao, Qishu; Wang, Chunlu; Zheng, Yaxin; Pan, Xiaohui; Zhong, Wenying; Xu, Keming
Abstract: The use of lonidamine (LND) in photodynamic therapy (PDT) provides a viable approach to develop low-dose PDT modules with high efficacy, for LND potentiates cytotoxicity of photosensitizers through dysregulation of mitochondrial function. Yet, the efficacy of LND is restricted by its low accumulation in cancer cells, especially in the mitochondrial compartments. To address the problem, we design an LND-derived self-assembling peptide molecule (LND-K) that dually targets integrin receptors and mitochondria of cancer cells. The targeted cellular delivery of LND-K gives higher efficacy in ablation of mitochondrial function in melanoma cells A375, as compared to free LND or the control molecule that lacks mitochondria-targeting moieties. To integrate LND-K in a typical PDT module, we develop a nanofibrillar hydrogel system through co-assembly of LND-K and TPPS4, an anionic photosensitizer that forms tight electrostatic interactions with cationic residues of LND-K. Notably, hydrogel formulation of LND-K/TPPS4 facilitates slow release of TPPS4 over 14 days in vitro, and displays a longer retention time than aqueous solution of TPPS4 in vivo . By integrating a mitochondria-targeted molecule (LND-K) in a typical PDT module, we achieve synergistic killing of A375 cells with dual drugs, where LND-K not only serves as a chemotherapeutic drug, but also potentiates the cytotoxicities of TPPS4 toward A375 cells in vitro and in vivo . The peptide-based drug self-delivery system promises the development of efficacious combination treatments against cancer, that integrate cell sensitization with existing anticancer modules ( e.g., chemotherapy and PDT) for enhanced therapeutic efficacy. Statement of significance: This study reports the design and synthesis of a lonidamine (LND)-derived self-assembling peptide (LND-K) that dually targets integrin receptors and mitochondria of cancer cells. Under the precision guidance of a mitochondria-targeting sequence, LND-K-containing nanofibers target mitochondria and ablate mitochondrial functions. On one hand, the targeted delivery of LND-K reduces cell viabilities through a chemotherapy route; on the other hand, LND-K sensitizes cancer cells for subsequent PDT treatment with enhanced efficacy, which is mediated by induction of ROS, loss of mitochondrial membrane potential, and decrease of cellular ATP level. We believe that the design of mitochondria-targeted drug delivery systems with a self-assembling molecule provides a new approach to potentiate cytotoxicity of photosensitizers in a low-dose PDT module. Graphical abstract: Image, graphical abstract